2021
DOI: 10.3389/fpls.2020.610176
|View full text |Cite
|
Sign up to set email alerts
|

A Pathogenesis-Related Protein-Like Gene Is Involved in the Panax notoginseng Defense Response to the Root Rot Pathogen

Abstract: Pathogenesis-related proteins (PRs) are a class of proteins that accumulate in response to biotic and abiotic stresses to protect plants from damage. In this study, a gene encoding a PR-like protein (PnPR-like) was isolated from Panax notoginseng, which is used in traditional Chinese herbal medicines. An analysis of gene expression in P. notoginseng indicated that PnPR-like was responsive to an infection by the root rot pathogen Fusarium solani. The expression of this gene was induced by several signaling mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Pathogenesis-related (PR) genes, a class of defense-related genes, play important roles in plant resistance to biotic and abiotic stresses [ 51 , 56 , 78 , 79 , 80 , 81 ]. PR10 gene expression is induced in many plants by drought and salt stress [ 48 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenesis-related (PR) genes, a class of defense-related genes, play important roles in plant resistance to biotic and abiotic stresses [ 51 , 56 , 78 , 79 , 80 , 81 ]. PR10 gene expression is induced in many plants by drought and salt stress [ 48 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis-related (PR) genes are known to contribute to plant resistance to biotic stresses [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. However, there are also numerous studies showing that PR genes also confer tolerance to abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…They accumulate after pathogen invasions, and may act as antimicrobial agents mediating cell wall hydrolysis, contact toxicity, and perhaps defense signaling (Zhang et al, 2017 ). A recent study demonstrated that Panax notoginseng PR-like proteins can inhibit F. solani and C. gloeosporioides mycelial growth (Li et al, 2021b ). Another study proved that overexpressing the moss ( Physcomitrella patens ) PR10 gene in A. thaliana enhances plant resistance to Pythium irregulare (Castro et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the germplasm resources of Lilium species resistant to F. oxysporum have been used for breeding disease-resistant lines, little is known about their mechanisms regulating transcription during an infection by F. oxysporum . In a recent study, 35 WRKY genes were identified in L. regale after the transcriptomes of plants inoculated with F. oxysporum were sequenced (Li et al, 2021b ). At the transcriptional level, LrWRKY2 is highly responsive to methyl jasmonate (MeJA), salicylic acid (SA), ethephon (ETH), and hydrogen peroxide (H 2 O 2 ) treatments as well as F. oxysporum infections.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenesis-related proteins (PRs) are widely distributed in plants, including alfalfa, and are essential in defense responses. Their expression is regulated by specific hormone signaling pathways ( Li et al, 2021b ). These PRs proteins have different functions, i.e., production of hydrolytic enzymes such as glucanases and chitinases, which lysis cell wall components ( Sunpapao and Pornsuriya, 2016 ), thaumatin-like and osmotin-like proteins which weaken cell walls and permeabilized plasma membranes ( Rather et al, 2015 ), antimicrobial peptides ( Nawrot et al, 2014 ) and RNAse activities to degrade pathogens RNA ( Tang et al, 2019 ).…”
Section: Management Strategiesmentioning
confidence: 99%